2014
DOI: 10.1007/s12178-014-9240-0
|View full text |Cite
|
Sign up to set email alerts
|

Heat-related illness in sports and exercise

Abstract: Exertional heat-related illness (EHRI) is comprised of several states that afflict physically active persons when exercising during conditions of high environmental heat stress. Certain forms of EHRI may become life threatening if not treated. Exertional heat stroke (EHS), characterized by a core body temperature of >40°C and mental status changes, is the most severe form of EHRI. EHS must be treated immediately with rapid body cooling to reduce morbidity and mortality. Many EHRI cases are preventable by follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 89 publications
(69 reference statements)
0
26
0
2
Order By: Relevance
“…No questions about heat acclimatization were included in the questionnaire. Past studies indicated that heat acclimatization not only improves exercise capacity in hot environments 17) , but also prevents heat illness 18 , 19) . Indeed, the Japanese government requires strict heat illness preventive programs for workers who have not been acclimated to heat stress 20) .…”
Section: Discussionmentioning
confidence: 99%
“…No questions about heat acclimatization were included in the questionnaire. Past studies indicated that heat acclimatization not only improves exercise capacity in hot environments 17) , but also prevents heat illness 18 , 19) . Indeed, the Japanese government requires strict heat illness preventive programs for workers who have not been acclimated to heat stress 20) .…”
Section: Discussionmentioning
confidence: 99%
“…121 Additionally, recent evidence suggests that heat-related illness may be increasing with climate change. 122,123 Every year, lightning accounts for dozens of deaths in the United States, although data regarding the incidence among youth soccer participants are not available. 124 Precautions and simple strategies may reduce the risk of injury due to adverse environmental conditions.…”
Section: Environmental Safetymentioning
confidence: 99%
“…In this regard, hyperthermia is known to reduce physical and athletic performance [4,5], altering cardiovascular function and leading to both peripheral and central fatigue [6]. Furthermore, exertional heat stroke may occur when core temperature reaches 40 • C and the subject begins to suffer changes in mental status [7]. Nonetheless, highly trained endurance athletes respond physiologically as if they were already heat acclimatized [8], and present less adaptive potential in comparison with moderately trained athletes or untrained subjects [9].…”
Section: Introductionmentioning
confidence: 99%